Pengembangan Model Project-Based Learning untuk Meningkatkan Keterampilan Merias Wajah Penari Bugis Makassar Mahasiswa Tata Rias - Burhanuddin, Izmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a Project-Based Learning (PjBL)-based instructional model to improve the makeup skills of Bugis Makassar dancers among undergraduate students of the Family Welfare Education Study Program, Beauty Education Concentration. The study was motivated by the low level of students’ practical skills in applying local cultural makeup due to learning processes that were still dominated by demonstration methods and conventional practice, resulting in limited student activeness and creativity during the learning process.The study employed a Research and Development (R&D) approach by adapting the Borg and Gall development model. The research subjects consisted of 25 students enrolled in the Special Makeup course and involved expert validators in vocational education and Bugis Makassar cultural makeup. Data were collected through observation, interviews, documentation, questionnaires, and practical skill tests. The data were analyzed using descriptive qualitative and quantitative methods to determine the validity, practicality, and effectiveness of the developed instructional model. The results indicated that the Project-Based Learning instructional model met the criteria of being highly valid, practical, and effective. The first-stage validation obtained an average score of 77.6%, categorized as valid, while the second-stage validation increased to 91.4%, categorized as highly valid. Student learning activities after the implementation of the PjBL model achieved an average percentage of 88% in the very good category. In addition, students’ practical skills showed a significant improvement, with the average pre-test score increasing from 35.8 to 91 in the post-test, resulting in an improvement difference of 55.2 points. The findings demonstrated that the implementation of the PjBL model was able to enhance students’ creativity, practical skills, teamwork, and active participation in learning the makeup techniques of Bugis Makassar dancers. Therefore, the Project-Based Learning-based instructional model can be used as an innovative learning alternative in local culture-based vocational beauty education.